A formação docente e o currículo escolar: o navegar da abordagem temática - Silva, Josiane Marques da (2023)
This thesis, of a qualitative nature, aims to discuss possible connections between the School Curriculum, within the scope of the Thematic Approach, with Teacher Training, especially in the context of training processes. The research problem is: how do researches in Science Education that deal with the curricular field of the Thematic Approach articulate with Teacher Training? To respond to the problem, methodological paths were taken. The first is characterized by the bibliographical research in the minutes of the Encontro Nacional de Pesquisa em Educação em Ciências (ENPEC) on Training Needs and Curriculum. From the analyzes of the productions, the first being carried out through scientometric analysis, it was possible to map the Brazilian regions in which the research was published, the postgraduate programs and the Higher Education Institutions of origin. And, through the Discursive Textual Analysis, it was possible to verify how the Formative Needs are understood and discussed in these works, as well as to understand how the Formative Needs are articulated with the curricular discussions in the works that deal with processes of teacher formation. However, there was silence on the articulations of Training Needs with curricular issues, such as the absence of discussions on the Thematic Approaches in Freire's perspective and discussions on the National Common Curricular Base. Thus, the horizons of the research were re-dimensioned, in which, from the silences, it began to investigate the articulations of the curricular field of the Thematic Approach with teacher training. For this, a bibliographical study was carried out in theses and dissertations on the articulations between teacher training and the Thematic Approach. As a result of the process, analyzed through Discursive Textual Analysis, two analytical categories emerged I. Curriculum making in the Thematic Approach – navigating through training processes and II. Training processes at ATF – Permanent training intertwined with Freire's curriculum. From the results obtained in this bibliographical study, the need emerged to deepen some theoretical elements to better understand the articulations between teacher training and the Thematic Approach. As a summary of the results, it is highlighted that the movements for the establishment and extension of the Thematic Approach emerged from teacher training contexts. It is pointed out that the articulations between the field of the Thematic Approach and teacher training are found in the Permanent formative processes, especially in the processes of obtaining the Themes, in which the themes are the structuring of curricula within the Thematic Approach. Finally, a Nautical Chart was elaborated in which territories/borders necessary for the realization of permanent formative processes in the context of the curricular making of the Thematic Approach are presented.